Semiotics, photography, and social justice: on the border between Semiotics of Photography and Semiotics of Law - Bittar, Eduardo Carlos Bianca (Estudos Semióticos, 2023)
This paper develops a semiotic analysis of photography, discussing its value for public debate, the awareness and mobilization of the public opinion and the struggle for social justice. The proposed analysis seeks to follow the fine line between the Semiotics of Photography and the Semiotics of Law, in order to bring two fields of work closer that have only been slightly explored, at least within the theoretical perspective of Greimasian semiotics. Photography is analysed as photographic text, inserted in cultural narratives, in order to stabilize the photographic image, mobilizing socio-cultural meanings that, when discussing questions of justice, they are able to affect other discourses. By generating the affectation of mentalities, the image has the power of persuasion, generating a favourable cycle for the implementation of policies and actions favourable to new rights. It is in this way that photographic text influences, directly or indirectly, the affirmation of social justice and, for this reason, it can be in the genesis of legal text.